Priests, tongues, and rites : the London-Leiden magical manuscripts and translation in Egyptian ritual (100-300 CE) - Dieleman, Jacco (Religions in the Graeco-Roman world, 2005)
This study of two related Demotic-Greek magical handbooks provides new information about the interaction between native Egyptian priests and the Hellenized elite of Roman-period Egypt through a careful analysis language interference, textual layout, religious imagery and ritual techniques.